2021
DOI: 10.1002/1348-9585.12259
|View full text |Cite|
|
Sign up to set email alerts
|

A cross-sectional study of infection control measures against COVID-19 and psychological distress among Japanese workers

Abstract: Objectives This study examined the relationship between the status of infection control efforts against COVID‐19 in the workplace and workers' mental health using a large‐scale Internet‐based study. Methods This cross‐sectional study was based on an Internet monitoring survey conducted during the third wave of the COVID‐19 epidemic in Japan. Of the 33 302 people who participated in the survey, 27 036 were included in the analyses. Participants answered whether or not ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
(40 reference statements)
4
27
0
Order By: Relevance
“…Moreover, an absence of RSH was a significant risk factor of psychological distress. Previous studies have described RSH as a particularly important risk factor of deteriorating mental health among workplace infection control measures [ 2 , 3 ], a finding that was replicated in the present study. Therefore, both long working hours and an absence of RSH were revealed to be risk factors of mental health deterioration.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Moreover, an absence of RSH was a significant risk factor of psychological distress. Previous studies have described RSH as a particularly important risk factor of deteriorating mental health among workplace infection control measures [ 2 , 3 ], a finding that was replicated in the present study. Therefore, both long working hours and an absence of RSH were revealed to be risk factors of mental health deterioration.…”
Section: Discussionsupporting
confidence: 85%
“…Workers without RSH had a significantly higher risk of psychological distress due to long working hours than those who worked with RSH. As mentioned earlier, previous studies reported that long working hours [ 7 , 8 ] and RSH [ 2 , 3 ] are important for mental health. Our study extends prior findings by revealing that the absence of RSH in the workplace could result in a stronger association between long working hours and psychological distress.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[24][25][26] In addition, we have reported that the more the workplace IPC measures are implemented in a workplace, the lower the psychological distress among workers. 27 Workplace IPC measures may contribute to improved work engagement by decreasing employees' anxiety and mental stress. However, it is unclear whether these IPC measures are effective in reducing the risk of actual COVID-19 infection; another study is needed to clarify this research question.…”
Section: Discussionmentioning
confidence: 99%